Website Sustainability Disclosure Analysis: A Case of Publicly-Listed Mining Companies in the Philippines - Tubay, Jerwin B.; De Leon, Myra V. (International Journal of Energy Economics and Policy, 2019)
This study determined whether the mining company's age, size, profitability and location of mining operations caused differences in level of their sustainability disclosure. Additionally, correlation among these variables is tested. The level of sustainability disclosure was measured using content analysis whereas the age, size, profitability and location are from financial statements and databases. The significant difference was tested using Kruskal Wallis while correlation was tested using Spearman Correlation. The result showed that the differences in the level of disclosures are statistically significant in terms of their sizes and that sustainability disclosures and the size is significantly and positively correlated. Keywords: Website disclosure, Mining Company, Sustainability JEL Classifications: Q53, Q56 DOI: https://doi.org/10.32479/ijeep.8347